Examining the moderating effects of race/ethnicity and socioeconomic status on the association between substance misuse and mental health in adolescence - Hatch, Kyle, author; Riggs, Nathaniel R., advisor; Prince, Mark, committee member; Luong, Gloria, committee member (Colorado State University. Libraries, 2022)
Adolescence has been shown to be a critical time for healthy development, however, research has suggested that substance use is high during this developmental period. Adolescent substance use is of concern, as it can lead to negative developmental health outcomes. Specifically, adolescent cannabis use has been associated with mental health outcomes like depression. This thesis sought to investigate the relationship between adolescent cannabis use and depression, and to test potential moderators such as race/ethnic identity and socioeconomic status (SES) in this relationship. It was found that adolescent cannabis use, along with assigned female sex at birth and low-SES, were associated with increased depressive symptoms in adolescence. Race/ethnic identity and SES did not significantly moderate the relationship between adolescent cannabis use and depression. Implications of these findings and suggestions for future studies are discussed.
Keywords: cannabis; ethnicity; adolescence; SES; depression